2020
DOI: 10.3390/ma13020297
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Mechanical Properties of 3D Printed ABS as a Function of Raster Angle

Abstract: Due to the rapid growth of 3D printing popularity, including fused deposition modeling (FDM), as one of the most common technologies, the proper understanding of the process and influence of its parameters on resulting products is crucial for its development. One of the most crucial parameters of FDM printing is the raster angle and mutual arrangement of the following filament layers. Presented research work aims to evaluate different raster angles (45°, 55°, 55’°, 60° and 90°) on the static, as well as rarely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…According to an experiment conducted by Dawoud et al [ 43 ], it was observed that since there is no pressure applied during the process of FDM, the final parts contain more void regions inside the printed structure. These void regions can be minimized by employing a smaller layer thickness as it enhances the bond between layers, which reduces the interlayer distortion that causes micro voids in the structure [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. When printing ABS using the FDM process, the process parameters such as infill density, orientation, layer thickness, airgaps, raster angle and width play important roles in providing better strength to the print part [ 51 , 52 ].…”
Section: Fused Deposition Modelling Of Thermoplastic Polymersmentioning
confidence: 99%
“…According to an experiment conducted by Dawoud et al [ 43 ], it was observed that since there is no pressure applied during the process of FDM, the final parts contain more void regions inside the printed structure. These void regions can be minimized by employing a smaller layer thickness as it enhances the bond between layers, which reduces the interlayer distortion that causes micro voids in the structure [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. When printing ABS using the FDM process, the process parameters such as infill density, orientation, layer thickness, airgaps, raster angle and width play important roles in providing better strength to the print part [ 51 , 52 ].…”
Section: Fused Deposition Modelling Of Thermoplastic Polymersmentioning
confidence: 99%
“…Therefore, a large number of research papers are dedicated to this matter. The vast majority of studies are experimentally based, using commercially available 3D printers, and focused on the tensile strength and elastic properties of PLA [ 11 , 21 , 22 ] ABS [ 5 , 10 , 11 , 23 , 24 , 25 ] and ASA [ 11 ]. Aforementioned research papers are based upon different specimen patterns, raster angles and infill percentage.…”
Section: Introductionmentioning
confidence: 99%
“…Several building parameters are used to define the FDM manufacturing process, namely the part build orientation, which defines the orientation of the part with respect to the planar domain of the nozzle (see Figure 1); the raster angle, which characterizes the orientation of inner filaments within the part with respect to the principal manufacturing axis; or the number of contours, which represents the number of adjacent filaments that follow the outer shape of the printed specimen. Domingo-Espin et al [7], Croccolo et al [8] and Galeja et al [9] studied the tensile properties of PC and ABS parts when varying the layer orientation, raster angle, and number of contours. Ziemian et al [10,11], and Li et al [12] described how the air gap and raster angle affect the tensile performance of ABS specimens.…”
Section: Introductionmentioning
confidence: 99%